Hydrogen generation by steam reforming of tar model compounds using lanthanum modified Ni/sepiolite catalysts. (15th March 2019) - Chen, Mingqiang; Li, Xiaojing; Wang, Yishuang; Wang, Chunsheng; Liang, Tian; Zhang, Han; Yang, Zhonglian; Zhou, Zhongshan; Wang, Jun
Graphical abstract: Highlights: Sepiolite (SEP) was applied into steam reforming of tar model compounds. Ni/La-SEP presented a promising potential for hydrogen production from SRPE. The Ni dispersion and metal-support interaction were improved by La addition. The highest carbon conversion and H2 yield was obtained for Ni/10La-SEP. La successfully suppressed the sintering and coking of Ni/SEP catalyst. Abstract: The paper describes the preparation of Ni/ x La-SEP catalysts selected low-cost clay minerals as support that possess high catalytic performance for steam reforming of phenol-ethanol (SRPE) to sustainably produce hydrogen. The catalysts were characterized using inductively coupled plasma optical emission spectrometry (ICP-OES), N2 adsorption-desorption, X-ray diffraction (XRD), H2 pulse chemisorption, high-resolution transmission electron microscopy (HRTEM), hydrogen temperature programmed reduction (H2 -TPR) and X-ray photoelectron spectroscopy (XPS). The results demonstrated that the addition of La reduced the active metal size and increased the active metal surface of the Ni/SEP catalyst. The Ni/10La-SEP catalyst exhibited the smallest active metal size (5 ± 0.5 nm) and highest active metal surface area (12.7 m 2 /gcat. ). As expected, Ni/10La-SEP presented the highest carbon conversion and H2 yield (92.1 and 87.6%, respectively) during SRPE reactions. Moreover, the La addition enhanced the steam reforming (SR) of CH4 and water-gas shift (WGS) reactions and successfully suppressed the sintering and coking of the Ni/SEP catalyst.